STRATEGI PERENCANAAN PENDIDIKAN ISLAM UNTUK MENINGKATKAN MUTU PENDIDIKAN - Mumtazah, Raihanatul; Mutiara, Mutiara; Sabbina, Aulia Rizkie; Rizki, Dinda (Universitas Dharmawangsa, 2025)
In the field of Islamic education, strategic planning is one of the key factors in the effectiveness of implementing educational activities and improving quality, in order to achieve the expected educational goals for each level and type of education at the national and local levels. Islamic education planning must be adapted to current developments. This includes developing a learning strategy curriculum. Islamic educational institutions must improve the quality of education through self-evaluation and improving the quality of teachers. The method used in this research is a type or library approach (Library Research).